2021
DOI: 10.1016/j.isci.2021.102287
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage uptake by mammalian cell layers represents a potential sink that may impact phage therapy

Abstract: Summary It is increasingly apparent that bacteriophages, viruses that infect bacteria and more commonly referred to as simply phages, have tropisms outside their bacterial hosts. Using live tissue culture cell imaging, we demonstrate that cell type, phage size, and morphology play a major role in phage internalization. Uptake was validated under physiological conditions using a microfluidic device. Phages adhered to mammalian tissues, with adherent phages being subsequently internalized by macropino… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
119
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(122 citation statements)
references
References 75 publications
3
119
0
Order By: Relevance
“…Bacteriophage presence in tissues is defined by the difference between phage accumulation and clearance. The accumulation depends on bacteriophage capacity to be captured by mammalian cells, the feature that is mainly referred to cellular uptake via micropinocytosis and transcytosis [ 28 ]. The size of bacteriophage particles as it has been shown in in vitro experiments is one of the important factors with larger particles to be less permeable [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteriophage presence in tissues is defined by the difference between phage accumulation and clearance. The accumulation depends on bacteriophage capacity to be captured by mammalian cells, the feature that is mainly referred to cellular uptake via micropinocytosis and transcytosis [ 28 ]. The size of bacteriophage particles as it has been shown in in vitro experiments is one of the important factors with larger particles to be less permeable [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation depends on bacteriophage capacity to be captured by mammalian cells, the feature that is mainly referred to cellular uptake via micropinocytosis and transcytosis [ 28 ]. The size of bacteriophage particles as it has been shown in in vitro experiments is one of the important factors with larger particles to be less permeable [ 28 ]. The clearance is believed to be exerted by immune cells, such as macrophages and B-cells [ 29 , 30 ] with no specific ligand-receptor interactions being found yet.…”
Section: Discussionmentioning
confidence: 99%
“…Novel preclinical models for studying phage kinetics There are multiple unknowns when studying phage kinetics, such as diffusivity through the body, as well as their interactions with the immune system and human cells, which may have important implications for phage-based modulations. To shed light on these, preclinical models with high accuracy are sought after [39,73]. 2D cultures in a microfluidic system that enable live-cell imaging under conditions similar to the human body have recently been used for studying phage kinetics.…”
Section: The Limitations Of Phages and The Help Of Emerging Technologiesmentioning
confidence: 99%
“…2D cultures in a microfluidic system that enable live-cell imaging under conditions similar to the human body have recently been used for studying phage kinetics. They showed that phages are rapidly internalised by the endothelial cells through micropinocytosisthe uptake rate was significantly affected by the size and morphology of the phage as well as by the cell types tested [73]. Yet, despite their popularity, 2D cultures do not truly represent how cells live and function in situ, suggesting an inevitable shift from 2D to 3D cell cultures.…”
Section: The Limitations Of Phages and The Help Of Emerging Technologiesmentioning
confidence: 99%
“…Such studies provide valuable data on immune responses, safety, efficacy and toxicity to support phage treatment of pathogenic bacteria in clinical settings [ 52 , 53 , 54 ]. Cell lines that have been used in phage studies include several human cerebral microvascular endothelial cells, epithelial cells most commonly HeLa, A549 and HT29 from the cervix, lung and colon, respectively [ 52 , 53 , 55 ]. Useful fibroblast cell lines used include BJ from human skin, the endothelial cell line HUVEC from umbilical veins, and monocyte-induced macrophages-THP-1 cells [ 55 ].…”
Section: Efficacy Testing In Complex In Vitro Infection Modelsmentioning
confidence: 99%